MODEL PEMBELAJARAN STUDENT-CENTERED DALAM PAI - Puji Roudlotul Adni; Hilal Tafattuhil Arzaq; Irsyad Kama Fahreza; Hafidz Al Faqih; Nabila Salsa Hidayah; Faiq Agustian Hamda; Rodianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The shift in educational paradigms in the modern era demands a learning process that is no longer teacher-centered, but rather provides more space for students to be involved in building their own knowledge. The Student-Centered Learning model comes as a learning approach that positions students as the main subjects in the learning process through active, reflective, collaborative, and contextual activities. The aim of this study is to describe the student-centered learning model in Islamic Religious Education (PAI). This research uses a qualitative approach with a literature study method. The findings indicate that in the context of Islamic Religious Education, the student-centered approach allows the learning process to go beyond simply delivering normative material, developing instead into a process of internalizing Islamic values through learning experiences that are close to the students' lives. Students are encouraged to understand the meaning of religious teachings more deeply, reflectively, and practically, so that religious awareness is formed not just as a formality but is also reflected in daily attitudes and behaviors. In this way, Student-Centered Learning is seen as a learning approach that can be relevant in shaping students who are critical, creative, adaptive, and have a strong religious character in line with the demands of 21st-century education.